Deciphering the dose-dependent effects of thymoquinone on cellular proliferation and transcriptomic changes in A172 glioblastoma cells - Rachana Pandey; Purushothaman Natarajan; Umesh K. Reddy; Wei Du; Cristian Sirbu; Moussa Sissoko; Gerald R. Hankins (PLoS ONE, 2025)
Glioblastoma multiforme (GBM), the most prevalent primary malignant brain tumor in adults, exhibits a dismal 6.9% five-year survival rate post-diagnosis. Thymoquinone (TQ), the most abundant bioactive compound in Nigella sativa, has been extensively researched for its anticancer properties across various human cancers. However, its specific anti-cancer mechanisms and pathways in glioblastoma remain to be completely elucidated. In this study, we assessed the impact of different TQ concentrations on the viability of A172 cells using WST-8 and Toluidine blue assays, followed by RNA sequencing (RNA-Seq) to identify differentially expressed genes (DEGs). We confirmed their expression levels through quantitative RT-PCR and performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses for these DEGs. RNA-seq revealed no significant gene expression changes at 2.5 μM and 5 μM TQ concentrations. However, at 25 μM and 50 μM, TQ significantly reduced cell viability dose-dependently. We identified 1548 DEGs at 25 μM TQ (684 up-regulated, 864 down-regulated) and 2797 DEGs at 50 μM TQ (1528 up-regulated, 1269 downregulated), with 1202 DEGs common to both concentrations. TQ inhibited key pathways such as PI3K-Akt signaling, calcium signaling, focal adhesion, and ECM-receptor interaction in A172 cells. It downregulated several potential oncogenes (e.g., AEBP1, MIAT) and genes linked to GBM proliferation and migration (e.g., SOCS2, HCP5) while modulating Wnt signaling and up-regulating tumor suppressor genes (e.g., SPRY4, BEX2). TQ also affected p53 downstream targets, maintaining p53 levels. This study elucidates the anti-cancer mechanisms of TQ in A172 GBM cells, underscoring its effects on multiple signaling pathways and positioning TQ as a promising candidate for innovative glioblastoma treatment strategies.